PERAN MAQASID SYARIAH DALAM MEMELIHARA KEDUDUKAN AGAMA ISLAM DI MALAYSIA - Ayu Nor Azilah; Mohamed Ali Haniffa; Wayu Nor Asikin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
This article discusses Maqasid Shariah upholding the position of Islam as the official religion of Malaysia as enshrined in the Federal Constitution. However, other religions are allowed to be practiced freely for as long as it does not interfere with public order. The upholding of Islam is as stated in Article 3 (1) of the Federal Constitution of Malaysia through the Malay Rulers at state level and the Yang di-Pertuan Agong at the Federal level, the establishment of the Islamic Religious Council in each state and also the responsibility of the National Council of Religious Affairs. This is because Islam is the religion of Allah S.W.T. and it is the greatest gift to save and protect people from catastrophes. This study uses secondary sources and library research methods. The findings show that the position of Islam in Malaysia is upheld through the implementation of Maqasid Shariah. This is in line with the current situation of plural society in Malaysia where everyone is given freedom to practice their religion and culture.